Hand washing as an effective technique for intestinal parasites control among school children in Gaza city: Hand washing as an effective technique for intestinal parasites control - Alhindi, Adnan; Al-karirri, Moeen; kanoa, Basil; Abu Ouda, Samaher S.; Erqyq, Yasmeen M.; Radwan, Amal I.; Jalambo, Marwan O. (Jour Med Resh and Health Sci, 2021)
Background/aim: Hand washing is one of the most effective ways to prevent the spread of many types of infection and illness especially those spread through oral-fecal route. Intestinal parasites are parasites that populate the gastrointestinal tract in humans and other animals they can live throughout the body, but most prefer the intestinal wall. Intestinal parasitic infections are among the most common infections worldwide. The high prevalence of parasites infection in children is attributed to many factors, particularly environmental and personal hygiene We aimed to assess the using of hand washing technique for the controlling of intestinal parasites infection among school children in Gaza. Method: 508 children from primary school children were examined for the presence of intestinal parasites and then the infected children were divided into case and control groups based on match criteria. Hand washing and health education were applied on intervention group and then the second stool sample was examined from both case and control groups. Results: the prevalence of intestinal parasitic among school children was 23.2%. Entamoeba histolytica/dispar was the highest protozoa detected among school children in this study (73.3%). The prevalence of intestinal parasites among children was reduced after the application of hand washing technique from 23.2% to 15.5%, the prevalence of intestinal parasites in male higher than female due to variant behavior of both sexes. Conclusion: It is concluded that hand washing has a significant role in reducing intestinal parasitic infection among school children. It is recommended that hand washing should be delivered to all school children in Gaza strip.